Delayed traumatic diaphragmatic rupture: diagnosis and surgical treatment - Zhao, Luo; Han, Zhijun; Liu, Hongsheng; Zhang, Zhiyong; Li, Shanqing (Journal of Thoracic Disease, 2019)
Background: To investigate the diagnosis and surgical therapy of delayed diaphragmatic rupture. Methods: Forty patients with traumatic diaphragmatic rupture with delayed presentation and diagnosis were collected in Peking Union Medical College Hospital from 2000 to 2018, and a retrospective analysis was performed. Results: In all forty patients, 36 (90%) patients had a traumatic past history, and 32 (80%) patients had clinical manifestations when diagnosed. Left-sided diaphragmatic rupture was found in 32 (80%) patients and right in 8 (20%) patients. One patient received emergency surgery, and 39 received selective surgery. Thirty-eight patients received thoracotomy, and 2 patients received combined thoracic-abdominal surgery. Thirty-six patients received direct diaphragm suture, and 4 patients received mesh repair. One patient had an intestinal obstruction and received enterolysis 19 days after surgery. During follow-up, 1 patient experienced recurrence 2 years later. Conclusions: Careful recording of past history and physical examination are the best approaches in diagnosing delayed presentation of traumatic diaphragmatic rupture. CT scan with reconstruction of the diaphragm is helpful in both diagnosis and differential diagnosis. Surgical therapy after diagnosis is the best treatment.